2017
DOI: 10.4238/gmr16029696
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic correlations between soybean agronomic traits and path analysis

Abstract: The goals of this research were to evaluate the phenotypic and genotypic correlations between agronomic traits, to perform path analysis, having as main character grain yield, and to identify indirect selection criteria for grain yield. The experiment was carried out in an experimental area located at Capim Branco farm, which belongs to Federal University of Uberlândia, during the growing season of 2015/2016.Twenty-four soybean genotypes were evaluated under randomized complete block design with three repetiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 11 publications
5
23
0
1
Order By: Relevance
“…The correlation coefficient is useful for measuring the degree and direction of association between traits. However, it can generate deceptive results because the high degree of correlation between two traits may happen due to the indirect effect of a third one (Cruz et al, 2012) (as cited in Machado et al, 2017). Consequently, it is necessary to examine the cause and effect relationship between variables.…”
Section: Path Analysismentioning
confidence: 99%
“…The correlation coefficient is useful for measuring the degree and direction of association between traits. However, it can generate deceptive results because the high degree of correlation between two traits may happen due to the indirect effect of a third one (Cruz et al, 2012) (as cited in Machado et al, 2017). Consequently, it is necessary to examine the cause and effect relationship between variables.…”
Section: Path Analysismentioning
confidence: 99%
“…number of reproductive nodes and number of branches, had a significant phenotypic and genotypic correlation to the seed yield respectively (Table 1). Machado et al (2017) also reported that number of branches had significant genotypic and phenotypic correlation to seed yield. These two characters had a important role in the increase of seed yield per plant.…”
Section: Indirect Effectmentioning
confidence: 96%
“…Genetic correlation involves a relationship of heritable nature that allows heritable selection between the traits. Therefore, the study of genetic correlation is crucial to identifying the traits that can be used as an indirect selection for grain yield (Machado et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…All these differences might be explained by a genetic basis. The authors have demonstrated, that a high correlation between phenotypic and genotypic variability (Machado et al, 2017) exists. Ultimately, the relative regularity of the genotypes in the plane allows us to accept that for this experiment, we used an important and representative sample amount of the available genetic resources of common beans in Ecuador, and the others introduced from Colombia.…”
Section: Principal Components Analysis (Pca)mentioning
confidence: 97%